DEVELOPMENT OF THE P5 DIGITAL MODULE PLATFORM: POTENTIAL LOCAL WISDOM OF CIREBON IN THE MERDEKA CURRICULUM - Naura Lathifah Jayadi; Prihantini; Yayang Furi Furnamasari (Jurnal Cakrawala Pendas, 2024)
This research aims to develop a digital module for P5 focusing on the local wisdom of Cirebon, particularly shell crafts, to support the implementation of the Kurikulum Merdeka in elementary schools for fourth-grade student. The methodology employed is the 4D model, which consists of four stages: Define, Design, Develop, and Disseminate. The needs analysis in the Define stage highlights the importance of a module relevant to local wisdom. The Design stage involves creating engaging storyboards and visuals, while the Develop stage includes creating the module using Canva and Photoshop, followed by validation from subject matter and media experts. Validation results indicate that the module is highly suitable for use, with scores of 93.18% and 97.72% for content validation, and 84.61% and 88.46% for media validation. During the Disseminate stage, the module was introduced in several schools and received positive feedback. The main findings show that the module is effective in enhancing student engagement, with positive response percentages exceeding 82%, particularly in language use, which reached 91.3%. This research confirms that the P5 digital module themed on Cirebon's local wisdom can meet educational needs and positively impact the teaching-learning process in Elementary School.